A documentation of calcaneus region diabetic foot care: Wound healing during outpatient treatment - Sylvia, Ester Inung (GHMJ (Global Health Management Journal), 2022)
Summary: Patients with diabetes are vulnerable to infection and poor healing after injury. Wound care using the steps and techniques described can achieve healing over time. Post healing care instructions are an important part of successful treatment Photos of the wound healing process are a good way to document the effects of treatment and provide a record for the health care team. Such photos can also be used to encourage patients with new wounds to work hard to obey care instructions